Intramuscular Delivery of Gene Therapy for Targeting the Nervous System - Tosolini, Andrew P.; Sleigh, James N. (Frontiers in Molecular Neuroscience, 2020)
Virus-mediated gene therapy has the potential to deliver exogenous genetic material into specific cell types to promote survival and counteract disease. This is particularly enticing for neuronal conditions, as the nervous system is renowned for its intransigence to therapeutic targeting. Administration of gene therapy viruses into skeletal muscle, where distal terminals of motor and sensory neurons reside, has been shown to result in extensive transduction of cells within the spinal cord, brainstem and sensory ganglia. This route is minimally invasive and therefore clinically relevant for gene therapy targeting to peripheral nerve soma. For successful transgene expression, viruses administered into muscle must undergo a series of processes, including host cell interaction and internalisation, intracellular sorting, long-range retrograde axonal transport, endosomal liberation, and nuclear import. In this review, we outline key characteristics of major gene therapy viruses – adenovirus, adeno-associated virus and lentivirus – and summarise the mechanisms regulating important steps in the virus journey from binding at peripheral nerve terminals to nuclear delivery. Additionally, we describe how neuropathology can negatively influence these pathways, and conclude by discussing opportunities to optimise the intramuscular administration route to maximise gene delivery and thus therapeutic potential.